Greens meet geeks. (Economist, 2018)
The article deals with the adoption of blockchain technology by Japanese energy company Tepco. The company aims to make the electricity industry more decentralized. The concerns of the industry on the use of blockchain technology are addressed, including the safety of cryptocurrency blockchains. The scope of potential blockchain-energy businesses is also discussed.